Spatial correlation of embedded nanowires probed by X‐ray off‐Bragg scattering of the host matrix. Issue 4 (29th July 2021) - Tran, Thomas; Weng, Xiaorong; Hennes, Marcel; Demaille, Dominique; Coati, Alessandro; Vlad, Alina; Garreau, Yves; Sauvage-Simkin, Michèle; Sacchi, Maurizio; Vidal, Franck; Zheng, Yunlin
Abstract : The spatial correlation of vertically aligned Ni and CoNi alloy nanowires in an SrTiO3 matrix has been analysed through the scattering around the Bragg reflections of the host matrix. The study demonstrates that off‐Bragg scattering can be used in a selective and nondestructive way to study nano‐objects inside a crystalline layer in nanocomposites and stacked nanostructures. Abstract : It is shown that information on the spatial correlation of nano‐objects embedded in a crystalline matrix can be retrieved by analysing the X‐ray scattering around the Bragg reflections of the host matrix. Data are reported for vertically aligned Ni and CoNi alloy nanowires (NWs) in an SrTiO3 matrix. When the Bragg condition is fulfilled for the matrix and not for the NWs, the latter can be approximated by voids, and the scattering around the matrix reflections contains information on the self‐correlation of the NWs ( i.e. on their diameter d ) and on the correlation between NWs (interdistance D ). Nondestructive synchrotron X‐ray diffraction data provide information on these values averaged over large areas, complementing local transmission electron microscopy observations. The measurements show that off‐Bragg scattering around the matrix reflections can be exploited to study the spatial correlation and morphology of embedded nano‐objects, independently of their crystallinity or strain or the presence of defects.